MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN DENGAN MENERAPKAN METODE JARIMATIKA PADA SISWA KELAS II SD NEGERI KEMIJEN 02 SEMARANG - Soegijanti, Maria Magdalena (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
The purpose of this study was to describe the magnitude of the increase in the learning ability to count in class II students of SD Negeri Kemijen 02 semester 1 of the 2021/2022 academic year. After being taught to count multiplication using the Jarimatics method. The background of this researcher is the lack of optimal ability to calculate students' multiplication. Of the 28 students, only 6 students or 21.42% completed. The remaining 22 people or 78.58% have not been completed. The average value is 54.00 on a scale of 100. The reason is that multiplication is a very broad material. In addition, the method used by the teacher is still not optimal. Another reason is that the method used by the teacher is not quite right. This research is a class action research (CAR), which is carried out in cycles. This research was conducted in class II of SD Negeri Kemijen 02 Semester 1 Academic Year 2021/2022. Cycle 1 was held on September 20, 2022, while cycle 2 was on October 13, 2022. Research has proven that the Jarimatika method can improve the ability to calculate multiplication. There was an increase in the score of 71.07 and in cycle 2 it became 85.00 which means there was an increase of 13.93 or an increase of 49.75%.